An interdisciplinary study in initial teacher training - Virginia Larraz Rada; Cristina Yáñez de Aldecoa; Mercè Gisbert Cervera; Cinta Espuny Vidal (Springer, 2014)
This experiment of innovative university education shows the interdisciplinary work carried out in the studies of the Bachelor of Science in Education at the University of Andorra. The study was developed within two subjects: Communication Technology (TAC) and Cultural Heritage Education in Andorra. The main objective of this experiment is to foster the use of technological resources and digital materials, with the aim of drawing cultural heritage closer to the classroom. Based on a previous study of documentation and an analysis of online educational materials, the students have to design an e-book, which is understood to be digital material in the curricular field of cultural heritage. This digital material is a didactic proposal that focuses on the construction of knowledge by primary school students. During the elaboration of the materials the instructors introduce follow-up activities. The results of the experiment show that, from an interdisciplinary approach, and a problem-solving, learning-centered methodology, specific and transferable abilities in initial teacher training can be studied and evaluated.